2011
DOI: 10.19030/jabr.v25i1.1050
|View full text |Cite
|
Sign up to set email alerts
|

Economics & Religious Implications On Adult Literacy In Sub-Saharan Africa

Abstract: <p class="MsoNormal" style="margin: 0in 0.5in 0pt;"><span style="font-size: 10pt;"><span style="font-family: Times New Roman;">Although literacy rates have improved somehow in recent years, there are still large numbers of people that are illiterates in developing countries.<span style="mso-spacerun: yes;">&nbsp; </span>This paper examines the impact of public education expenditures, the percentage of urban population and religious affiliation on adult literacy rate in Sub-Sah… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 7 publications
2
5
0
Order By: Relevance
“…URBAN is statistically significant, meaning that for one unit increase of urban population, the gender gap in literacy will decrease by 0.0028 unit. It is also the same as we expected, Okpala and Okpala (2009) proved that urban population have a significant positive impact on literacy, because urbanization promotes human capital, we expect that the higher the urban population percentage, the lower the gender gap in literacy. As for religion variables, since we exclude CATHOLIC, we only consider LOGPROTESTANT and ISLAM.…”
Section: Journal Of Asian Developmentsupporting
confidence: 81%
See 3 more Smart Citations
“…URBAN is statistically significant, meaning that for one unit increase of urban population, the gender gap in literacy will decrease by 0.0028 unit. It is also the same as we expected, Okpala and Okpala (2009) proved that urban population have a significant positive impact on literacy, because urbanization promotes human capital, we expect that the higher the urban population percentage, the lower the gender gap in literacy. As for religion variables, since we exclude CATHOLIC, we only consider LOGPROTESTANT and ISLAM.…”
Section: Journal Of Asian Developmentsupporting
confidence: 81%
“…Chaudhary and Rubin (2011) used data in India to show that literacy is negatively related to the proportion of Islam adherents in the district. Okpala and Okpala (2009) examined the data of 34 Sub-Saharan countries, they showed that countries with larger Islam believers have lower adult and female literacy rates, compared to countries with larger Christianity believers, the reason is that the early church missionary movement promoted the establishment of schools, countries that benefited from the early Christian mission schools experienced higher literacy rate than other countries. Furthermore, many kinds of literature focused on religion and female education.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…University education across the world is known for freedom which includes speech, association, movement, thought, conscience and religion, among others Okpala and Okpala (2017) but the negative implications of such freedom on youth in a developing country like Nigeria is often ignored in-spite of several studies conducted on the relationship of such freedom with social problems such as cultism, Ajayi et al (2010), violent demonstrations Babalola (2016), sexual assault Eze (2013), armed robbery Smith, (2001) cited in Omonijo et al (2017), prostitution and examination misconduct Petters and Okon (2016) and unstable academic calendar. The problem of violent demonstration, most especially, has resulted in the death of several students in many tertiary institutions Peter and Ebimobowei (2015).…”
Section: Introductionmentioning
confidence: 99%